Anodic dissolution of gallium in alkali metal chloride melts - Oleg V. Tokarev; Vladimir A. Volkovich (Chimica Techno Acta)
Gallium and gallium based alloys can be potentially used in pyrochemical and pyroelectrochemical reprocessing of spent nuclear fuels, particularly for separating actinides and rare earth fission products. However, the electrochemical behavior of gallium in high temperature molten salt electrolytes is very little studied. The present work was aimed at investigating the processes taking place during anodic dissolution of gallium in fused alkali chlorides (the ternary 6NaCl–9KCl–5CsCl eutectic mixture) and determining the ratio of gallium chloro-species in different oxidation states formed and remained in the melt. The experiments were performed between 550 and 750 °C, and the anodic current density varied from 0.024 to 0.094 A/cm2. Anodic polarization and coulometry were used, and the results obtained demonstrated that two gallium species, Ga(I) and Ga(III), were formed as a result of gallium anodic dissolution. The ratio between these two oxidation states depended on temperature and anodic current density. The method of processing the experimental data and the calculated values of the ratio of gallium ionic forms in the system under various conditions are presented.